Strontium and Osteoporosis - Ferda Özdemir; Esra Esen (Galenos Yayinevi, 2004)
Osteoporosis (OP) is a condition of bone fragility resulting from micro-architectural deterioration and decreased bone mass. OP depends on the interaction of genetic, hormonal, environmental and nutritional factors. Chronically low intakes of vitamin D and possibly magnesium, zinc, fluoride and vitamins K, B12, B6 and folic acid may predispose to osteoporosis. Minerals and oligo elements affect the process of formation and resorption by direct and indirect effects on the bone cells. Strontium is a oligo element, which is found widespread in the nature, and suggested for the treatment of osteoporosis. Strontium's effection the bones depend on dose. High intake of Sr damage bones mineralization. When it is taken at low dose, for a long time, bone resorption is decreased but formation is increased. Trabecular and cortical bones both are increased with strontium.